Physical and chemical treatments of residual fibers from Cocos nucifera L. aiming application in cement composites (Research, Society and Development, 2022)
The work aimed to evaluate the coconut mesocarp fibers (Cocos nucifera L.) in natura and submitted them to physical and chemical treatments for application in Portland cement composites. In natura fibers were subjected to four different treatments: immersion in cold water at 21ºC; immersion in hot water at 90ºC; immersion in 5% NaOH aqueous solution; and immersion in 24% H2O2 and 4% NaOH aqueous solution. In natura and treated fibers were evaluated by X-ray diffraction, scanning electron microscopy, and Fourier-transform infrared spectroscopy. Calorimetric tests were used to assess the influence of fibers obtained from different treatments on the exothermic behavior of cement during hydration. The results indicated that all treatments increased the crystallinity index, especially the alkaline followed by bleaching treatment (41.2%). The calorimetry test suggested that in natura and hot water treated fibers inhibited the cement hydration significantly. On the other hand, cold water, alkaline, and alkaline followed by bleaching treatments exhibited greater potential for application in cementitious composites.